The Chosen: The Hidden History of Admission and Exclusion at Harvard, Yale, and Princeton, de Jerome Karabel - Moura, Bruno Azevedo (Saberes: Revista interdisciplinar de Filosofia e Educação, 2011)
KARABEL, Jerome. The Chosen: The Hidden History of Admission and Exclusion at Harvard, Yale, and Princeton. Boston, New York: Houghton Mifflin Company, 2005. 711 p.